Un terrain miné, un travail de déminage ou comment parler de l’oppression des femmes minorisées en tant que chercheuse de la majorité - Iavarone-Turcotte, Anne (2023)
Dans cet article, je présente la manière dont j’ai abordé, pour tenter de les atténuer, les risques découlant de ma prise de parole sur mon objet d’étude doctorale : l’oppression des femmes dans les minorités religieuses. Ces risques découlant de mon positionnement de féministe blanche occidentale, membre de la majorité libérale et laïque, et détentrice de nombreux privilèges associés à ces statuts, j’ai résolu de modifier symboliquement ce positionnement dans ma recherche. Pour ce faire, j’ai élaboré et appliqué une méthodologie réflexive dont l’un des aspects clés, présenté dans l’article, a été de (re)tourner mon regard critique vers moi.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; cours; discipline; inégalités; justice sociale; phi4336; philosophie; point de vue situé; premier cycle; privilèges; pédagogie; périodes historiques; québec; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Race, cultures, identités : une approche féministe et postcoloniale - Bentouhami, Hourya (Presses universitaires de France, 2015)
La race fut longtemps appréhendée dans un sens biologique,approche qui constitue l'une des formes les plus puissantes de l'idéologie raciste. À la suite de la disqualification scientifique et politique de ces catégorisations biologiques, le racisme fut relégué au rang de simple préjugé. Ou, qu'en est-il de la production continuée de la race à l'ère prétendument "post-raciale" ? En mélangeant une approche féministe , attentive à une compréhension des rapports sociaux de sexe, et une approche postcoloniale , l'ouvrage analyse les conditions historiques et épistémologiques de la production de la race dans des sociétés qui se sont constituées - politiquement et économiquement - sur l'esclavage et la colonisation. Il montre que le racisme n'a pas disparu et a pris, au gré du renouvellement des formes de l'économie mondialisée, une nouvelle configuration qui oblige à nous interroger sur la supposée opposition entre un racisme biologique et un racisme dit culturel, qui aurait entériné l'inexistence des races biologiques, mais selon lequel il y aurait des différences culturelles irréductibles entre les peuples.
Keywords: approches et analyses; cours; discipline; fem1000; féminisme postcolonial; histoire et politique; inégalités; philosophie; premier cycle; privilèges; racisme; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Notes toward a performative theory of assembly - Butler, Judith (Harvard University Press, 2015)
Judith Butler elucidates the dynamics of public assembly under prevailing economic and political conditions, analyzing what they signify and how. Understanding assemblies as plural forms of perfomative action, Butler extends her theory of performativity to argue that precarity - the destruction of the conditions of livability - has been a galvanizing force and theme intoday's highly visible protests.
Keywords: approches et analyses; corps; discipline; genre; inégalités; militance; performativité; philosophie; précarité; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques

Traite, prostitution, inégalité - MacKinnon, Catharine A. (M éditeur, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Section: 123 pages ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Tracking Epistemic Violence, Tracking Practices of Silencing - Dotson, Kristie (Hypatia, 2011)
oo often, identifying practices of silencing is a seemingly impossible exercise. Here I claim that attempting to give a conceptual reading of the epistemic violence present when silencing occurs can help distinguish the different ways members of oppressed groups are silenced with respect to testimony. I offer an account of epistemic violence as the failure, owing to pernicious ignorance, of hearers to meet the vulnerabilities of speakers in linguistic exchanges. Ultimately, I illustrate that by focusing on the ways in which hearers fail to meet speaker dependency in a linguistic exchange, efforts can be made to demarcate the different types of silencing people face when attempting to testify from oppressed positions in society.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices épistémiques; inégalités; justice; philosophie; sciences humaines; silenciation; systèmes d'oppressions; thématiques; témoignage; violences; vulnérabilité; éthique

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

The promise of happiness - Ahmed, Sara (Duke University Press, 2010)
« The Promise of Happiness is a provocative cultural critique of the imperative to be happy. It asks what follows when we make our desires and even our own happiness conditional on the happiness of others: 'I just want you to be happy', 'I'm happy if you're happy'. Combining philosophy and feminist cultural studies, Sara Ahmed reveals the affective and moral work performed by the 'happiness duty', the expectation that we will be made happy by taking part in that which is deemed good, and that by being happy ourselves, we will make others happy. Ahmed maintains that happiness is a promise that directs us toward certain life choices and away from others. Happiness is promised to those willing to live their lives in the right way. Ahmed draws on the intellectual history of happiness, from classical accounts of ethics as the good life, through seventeenth-century writings on affect and the passions, eighteenth-century debates on virtue and education, and nineteenth-century utilitarianism. She engages with feminist, antiracist, and queer critics who have shown how happiness is used to justify social oppression, and how challenging oppression sometimes causes unhappiness. Reading novels and films including "Mrs. Dalloway", "The Well of Loneliness", "Bend It Like Beckham", and Children of Men, Ahmed considers the plight of the figures who are challenged by, and themselves challenge, the attribution of happiness to particular objects or social ideals: the feminist killjoy, the unhappy queer, the angry black woman, and the melancholic migrant. Through her readings, she raises critical questions about the moral order imposed by the injunction to be happy. »–Quatrième de couverture.
Keywords: approches et analyses; bonheur; care; discipline; inégalités; philosophie; queer; racisme; représentations; sciences humaines; sexisme; systèmes d'oppressions; thématiques; études culturelles

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Femmes et développement humain: l'approche des capabilités - Nussbaum, Martha Craven (Des femmes-Antoinette Fouque, 2008)
"Application du concept de capabilité aux inégalités de genre. L'auteure évalue le niveau de développement d'un pays non pas à son PIB mais à la capacité du gouvernement à maintenir l'égalité entre les hommes et les femmes. Elle appelle au développement d'une pensée politique et économique attentive à ces disparités, tout particulièrement dans les pays du Sud."
Section: 444, [1] pages
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; développement; féminisme décolonial; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

La femme et le sacrifice : d'Antigone à la femme d'à côté - Dufourmantelle, Anne (Denoël, 2007)
On a sacrifié les femmes au nom d'à peu près tout : morale, religion, politique, amour, maternité... Aujourd'hui encore, malgré les discours d'émancipation, persistent viols, harcèlements, sévices conjugaux, interdits et humiliations. Le destin de la féminité en Occident serait-il sacrificiel? En témoignent ces grandes héroïnes qui foisonnent dans nos mythes, nos légendes d'amour, nos religions, les textes fondateurs de notre culture, toutes plus fascinantes les unes que les autres. Elles ont pour nom Iphigénie, Hélène, Penthésilée, Médé, Iseut ou Jeanne d'Arc mais elles sont aussi des sœurs, des voisines, des exilées, des femmes croisées tous les jours dans la rue, prises à leur insu dans des vies manquées, blanches... De quel sacrifice ignoré la vie de ces femmes se soutient-elle? De quelle façon ces figures mythiques circulent-elles dans notre inconscient? Dans un essai de mythologie quotidienne, Anne Dufourmantelle interroge et retourne les destins spectaculaires de ces héroïnes en les confrontant à ceux, anonymes, parfois tragiques, de ces proches inconnues. D'une écriture subtile, elle approche la secrète texture de nos névroses et déploie la dramaturgie, aussi énigmatique que salvatrice, d'une véritable érotique du sacrifice au féminin.
Donné en lecture: p.9-12
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; inégalités; mythologie; philosophie; premier cycle; psychanalyse; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; violences contre les femmes*

L'ONU, alliée des femmes ? Une analyse féministe du système des organisations internationales - Falquet, Jules (Multitudes, 2003)
Cet article analyse la stratégie du système onusien pour neutraliser les mouvements sociaux contestataires en les faisant « participer » à son projet de « bonne gouvernance » mondiale, à travers l’exemple du mouvement féministe latino-américain et des Caraïbes. En étudiant les « politiques de population » des institutions internationales et la question du micro-crédit pour les femmes, on voit comment l’ONU parvient à se présenter comme « alliée » des femmes et à embrigader dans son entreprise une partie du mouvement féministe, alors qu’elle applique des politiques désastreuses pour les femmes, en particulier pour les femmes pauvres du Sud.
Keywords: amérique latine; amériques; approches et analyses; capitalisme; caraïbes; cours; discipline; histoire et politique; inégalités; oppressions institutionelles; philosophie; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

L'énigme de l'égalité - Scott, Joan Wallach (Cahiers du Genre, 2002)
Il arrive fréquemment que les débats sur l’action positive aux États-Unis traitent séparément les questions relatives à l’égalité et à la différence, aux droits individuels et aux identités de groupe. Pourtant, ce sont là des couples de concepts interdépendants, chacun étant lié à l’autre dans une tension nécessaire. Les tensions se manifestent de façon spécifique selon la période historique et doivent être analysées en fonction du contexte politique qui les porte et non comme des choix moraux ou éthiques a-historiques. Cet essai explore trois paradoxes — qui sont des tensions insolubles — propres aux débats sur l’action positive : 1) l’égalité est un principe absolu et une pratique historique contingente ; 2) les identités de groupe définissent des individus et leur refusent la pleine expression ou réalisation de leur individualité ; 3) les revendications de l’égalité impliquent l’acceptation et le rejet de l’identité de groupe produit par la discrimination. Autrement dit, les termes de l’exclusion, qui fondent la discrimination, sont à la fois refusés et reproduits dans la demande d’inclusion.
Keywords: action positive; amériques; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire; histoire et politique; intersectionnalité; inégalités; philosophie; pol4102; premier cycle; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

La citoyenneté multiculturelle: une théorie libérale du droit des minorités - Kymlicka, Will (Éditions La Découverte ; Éditions du Boréal, 2001)
Les sociétés contemporaines deviennent de plus en plus des sociétés multiculturelles dans lesquelles les groupes minoritaires ethniques ou nationaux réclament une reconnaissance publique et les moyens de préserver leur identité culturelle. Une revendication qui n'est pas sans susciter des conflits qui menacent parfois l'unité territoriale des États. Pour Will Kymlicka, la réponse à cet enjeu devenu incontournable constitue aujourd'hui l'un des plus grands défis pour la démocratie. Son propos, dans ce livre devenu un classique de la théorie politique, est de défendre une nouvelle conception du statut et des droits des minorités culturelles.
Section: 357 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; citoyenneté; cours; discipline; discours dominant; europe; histoire et politique; inégalités; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

L'évidence de l'égalité des sexes : une philosophie oubliée du XVIIe siècle - Dorlin, Elsa (L'Harmattan, 2000)
Au XVIIe siècle, quatre philosophes, à quelques décennies d'intervalle, formulent en des styles très différents la thèse selon laquelle l'égalité entre les hommes et les femmes est une évidence, une vérité indiscutable. Marie de Gournay, Anna Maria Van Schurman, François Poullain de la Barre et Gabrielle Suchon, estiment que si les interdictions et les discriminations frappant les femmes perdurent, c'est que la querelle entre les défenseurs et les pourfendeurs du " Beau Sexe " est biaisée : les présupposés de la différence sexuelle rendent la question de l'égalité ou de l'inégalité des sexes indécidable.
Donné en lecture cours FEM1000: p.11-14 et 17-32
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; histoire des femmes*; histoire et politique; incontournable; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes